Multispecific Antibodies: DNA‐Mediated Assembly of Multispecific Antibodies for T Cell Engaging and Tumor Killing (Adv. Sci. 2/2020). Issue 2 (22nd January 2020) - Pan, Liqiang; Cao, Chan; Run, Changqing; Zhou, Liujuan; Chou, James J.
Abstract : Nucleic acid–mediated protein–protein assembly (NAPPA) represents a true modular means for preparing multispecific antibodies (MsAbs). In article number 1900973, James J. Chou and co‐workers prepare MsAbs displaying T‐cell engaging and tumor killing properties in vivo. NAPPA allows for the preparation of individual antibody modules separately, stored in an antibody library (middle cubic grid), which can be used to assemble a large variety of MsAbs immediately before use.